Understanding Health and Social Challenges for Aging and Long-Term Care in China. (March 2021) - Yang, Wei; Wu, Bei; Tan, Si Ying; Li, Bingqin; Lou, Vivian W. Q.; Chen, Zhuo (Adam); Chen, Xi; Fletcher, James Rupert; Carrino, Ludovico; Hu, Bo; Zhang, Anwen; Hu, Min; et al.
The second King's College London Symposium on Ageing and Long-term Care in China was convened from 4 to 5th July 2019 at King's College London in London. The aim of the Symposium was to have a better understanding of health and social challenges for aging and long-term care in China. This symposium draws research insights from a wide range of disciplines, including economics, public policy, demography, gerontology, public health and sociology. A total of 20 participants from eight countries, seek to identify the key issues and research priorities in the area of aging and long-term care in China. The results published here are a synthesis of the top four research areas that represent the perspectives from some of the leading researchers in the field.